Technical Development Direction of China Modern Tramcar - Hu Jigui; Liu Tianfu (机车电传动)
With the analysis of Tramcar development process and the main product technologies of Europe, the key technologies of Tramcar development were summarized, and the Tramcar development direction of China was indicated.